PRIORITAS UPAYA UKM UNTUK TERUS MEMPERBAIKI DIRI MENGHADAPI PERSAINGAN - Widuri, Retno (Performance, 2013)
The self-repairing capability of the development structure or innovation happens differently toward different industry and also the products. There are the differences in establishing the innovation capability of the Bandol’smakers in Banaran, Banyumas seen from the company’s measurement, operational time from the company and the educational background of the owners. The company’s measurement factor can has significant influence toward the process of establishing the innovation capability. Operational time factor can has significant influence toward the process of establishing the innovation capability. Also, the educational factor can has significant influence towardthe process of establishing the innovation capability. The implications are the Bandol’s Producers in Banaran, Banyumas need to increase the innovation capability based on the company’s type, because there are some companies that have low about this capability. Since The Company’s measurement, operational time from the company and educational background give the significant influence, therefore the owners should concern toward those variable. The increasing of the innovation capability needs to be done together with the company’s measurement, operational time and the education of the owners.